The Effect of Capital Expenditure, Personnel Expenditure, and General Allocation Fund on Regional Financial Independence In Jambi Province - Rian Anggara Putra; Haryadi Haryadi; Putri Intan Suri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the effect of Capital Expenditure, Personnel Expenditure, and the General Allocation Fund (DAU) on Regional Financial Independence in Jambi Province during the period 2007–2025. The study employed secondary data obtained from the Central Bureau of Statistics (BPS) of Jambi Province and the Directorate General of Fiscal Balance (DJPK). Using 19 annual observations, the data were analyzed through multiple linear regression with SPSS version 25. The results show that Capital Expenditure and Personnel Expenditure have a positive and significant effect on Regional Financial Independence, whereas the General Allocation Fund has a negative and significant effect. Simultaneously, the three independent variables significantly affect Regional Financial Independence. The coefficient of determination (R²) was 0.471, indicating that 47.1% of the variation in Regional Financial Independence can be explained by the independent variables. These findings imply that productive expenditure management can strengthen regional financial independence, while excessive dependence on transfer funds tends to weaken fiscal independence.